2019
DOI: 10.1001/jamadermatol.2019.1514
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Number-Needed-to-Biopsy Metric for the Diagnosis of Cutaneous Melanoma

Abstract: IMPORTANCE To date, no concerted effort has been made to date to evaluate the literature on number-needed-to-biopsy (NNB) metrics, particularly to account for the differences in clinician type and melanoma prevalence in certain geographic locations.OBJECTIVE To review and synthesize worldwide data for NNB for the diagnosis of cutaneous melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 47 publications
1
33
0
2
Order By: Relevance
“…Thus, NNE, melanoma thickness, and cumulative melanoma incidence are reasonable surrogate outcomes, and to assess efficacy of a particular intervention, studies should report between‐group differences in these metrics. In a systematic review of 46 studies, NNE ranged from 2.2 to 287, highlighting the need for standardization of NNE and its reporting, which may require structured clinical impression and pathologic diagnostic data collection (Nelson, Swetter, Saboda, Chen, & Curiel‐Lewandrowski, 2019). Furthermore, to facilitate comparisons across studies and devices, adhering to standards in dermatologic imaging is imperative, such as those proposed by the International Skin Imaging Collaborative (ISIC) (Marghoob, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, NNE, melanoma thickness, and cumulative melanoma incidence are reasonable surrogate outcomes, and to assess efficacy of a particular intervention, studies should report between‐group differences in these metrics. In a systematic review of 46 studies, NNE ranged from 2.2 to 287, highlighting the need for standardization of NNE and its reporting, which may require structured clinical impression and pathologic diagnostic data collection (Nelson, Swetter, Saboda, Chen, & Curiel‐Lewandrowski, 2019). Furthermore, to facilitate comparisons across studies and devices, adhering to standards in dermatologic imaging is imperative, such as those proposed by the International Skin Imaging Collaborative (ISIC) (Marghoob, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Nault et al [ 9 ], numbers needed to biopsy (NNB) for all skin cancers and melanoma were reported to be 3.4 and 21.4, respectively. In another recent meta-analysis by Nelson et al, NNB for melanoma was estimated from studies published between 2000 and 2018 which was 15.6 worldwide [ 10 ]. In the present study, NNB was 3.29 and 27.24 for diagnosis of all skin malignancies and melanoma, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…melanoma. This ranges from ∼2 for some dermatologists to ∼30 for primary care physicians (31). Thus, according to current clinical practices, any lesions with prior odds lower than 1/2-1/30 of being malignant are less likely to be biopsied.…”
Section: Toward Enhancing Pigmented Lesion Screening With Biomarkersmentioning
confidence: 99%